School Refusal and Absenteeism: Perception of Teacher Behaviors, Psychological Basic Needs, and Academic Achievement - Filippello, Pina; Buzzai, Caterina; Costa, Sebastiano; Sorrenti, Luana (Frontiers in Psychology, 2019)
School refusal (SR) is a complex problem that may be caused by different risk factors such as individual and contextual factors (Kearney, 2007; Maynard et al., 2018; Heyne et al., 2019). These mechanisms can be described in the context of self-determination theory (SDT). For these reasons, the purpose of the present study is investigate the relationship between teacher perceived psychological control and support, psychological basic needs, SR behavior, and academic achievement, on adolescent sample. It is hypothesized that teacher perceived psychological control and autonomy support play a role on need frustration and need satisfaction; in turn, need satisfaction could reduce while need frustration could promote SR behavior and number of absences. Finally, SR behavior and number of absences could reduce academic achievement. 263 students (196 females, 67 males) with an average age of 16.14 (SD = 1.35; range 13–20 years). SEM analyses with observed variables have shown that the final model fit well the data, χ2(8) = 16.34, p = 0.04, CFI = 0.96, SRMR = 0.04, RMSEA (90% CI) = 0.06 (0.01; 0.10), showing the following significant path: need satisfaction was positively predicted by perceived teacher support and negatively predicted by teacher perceived psychological control; need frustration was positively predicted by teacher perceived psychological control; number of absences was negatively predicted by need satisfaction; SR was positively predicted by need frustration; school achievement was negatively predicted by SR and number of absences. These results have several implications for the school context and the deepening of the construct of SR and absenteeism.